Shadow Puppet Videos to Stimulate Time Vocabulary Speaking Skills for Children Aged 4-6 Years - Kurnadi; Dewa Ayu Puteri Handayani (Universitas Pendidikan Ganesha, 2023)
A child who actively speaks does not necessarily have good language skills, and a child who tends to be quiet does not mean that the child experiences obstacles in his language aspect. This research aims to produce shadow puppet videos that can help children aged 4-6 years develop speaking skills using time vocabulary. This development research uses the Research and Development (R&D) method with the ADDIE model. The subjects involved in this research were early childhood children. The validity of the shadow puppet video was measured through an evaluation questionnaire assessed by two experts, namely a media expert and a material expert. This research uses qualitative statistical analysis to process descriptive and subjective data, such as expert reviews, criticism and suggestions. Based on these findings, it can be concluded that the development of shadow puppet videos to stimulate the speaking skills of children aged 4-6 years in using time vocabulary has very high validity. Therefore, this shadow puppet video can be used as media in the school environment to support the learning process.